Sudden Onset of Severe Pulmonary Hypertension in a Preterm Infant: A Case Report on the Role of Maternal Use of Serotonin Re-Uptake Inhibitors During Pregnancy and Concurrent Risk Factors - Isabella Buffoni; Silvia Buratti; Marisa F. Mallamaci; Stefano Pezzato; Elisabetta Lampugnani; Francesca Buffelli; Ezio Fulcheri; Ezio Fulcheri; Andrea Moscatelli (Frontiers Media S.A., 2022)
Persistent pulmonary hypertension of the newborn (PPHN) is a severe condition caused by failed circulatory adaptation at birth. Pulmonary hypertension is most common in full-term infants and rare in preterms, although it is increasingly diagnosed also in extremely preterm infants. Previous studies demonstrated the association between maternal use of selective serotonin re-uptake inhibitors during gestation and pulmonary hypertension. This brief report describes the complex physiopathological correlations that were identified in a case of severe pulmonary hypertension in a fetal growth restricted (FGR) preterm infant, with a history of maternal use of antidepressants during pregnancy. Perinatal factors, triggers and aggravating mechanisms caused a dramatic clinical course. Maternal history of escitalopram therapy throughout pregnancy was noted. Uteroplacental insufficiency, fetal hypoxia, FGR, preeclampsia, preterm delivery, antenatal steroids, and cesarean section were documented as concurrent risk factors. Myocardial immaturity and dysfunction, secondary to FGR and prematurity aggravated the hemodynamic compromise. The short time gap between pharmacological ductal closure and the onset of PPHN may suggest a cause-effect relationship, as observed in previous reports. Placental histopathologic findings are reported.